Kelley-Seegmiller Syndrome: Urolithiasis, Renal Uric Acid Deposits, and Gout: What is the Role of the Urologist? (2019)
Kelley-Seegmiller syndrome (KSS) is a disorder that occurs when there is a partial deficiency of the enzyme hypoxanthine guanine phosphoribosyl transferase. It is involved in the metabolism of purines, clinically manifesting as hyperuricemia, hyperuricosuria, gout arthritis, and urolithiasis. The aim of this article is to present the case of a 33-year-old male with KSS, with left ureteral colic, and a 5-mm, 323-HU ureteral calculi, successfully managed with conservative management. It is critical to recognize that most urologists are not familiar with this inborn metabolic error and 75% of these patients will be affected by urolithiasis, thus making it a very critical and significant disease in our practice. © 2018 S. Karger AG, Basel.